Reconsideration of the load-bearing functions of the plantar fascia and intrinsic foot muscles in the windlass mechanism - Hiroshi Shinohara; Yasuyuki Umezaki; Airi Ikeda; Takara Ikeda; Nao Tateyama (Scientific Reports)
Abstract This study aimed to explore the contributions of the plantar fascia and intrinsic foot muscles to medial longitudinal arch (MLA) support and the windlass mechanism under different toe extension angles in seated and single-leg standing postures. The study included 51 healthy adults (41 males, 10 females; mean age: 21.3 ± 1.2 years) with no history of lower extremity injuries or pain in the past 3 months. Ultrasound elastography was used to measure the stiffness of the plantar fascia and flexor digitorum brevis under toe extension angles of 0°, 15°, 30°, and 45°. Dorsal arch height and arch height index (AHI) were evaluated to assess MLA changes. The plantar fascia and flexor digitorum brevis contributed to the windlass mechanism in the seated posture, while in the standing posture, the flexor digitorum brevis played a more pronounced role, with stiffness approximately six times greater than in the seated posture. The AHI was significantly higher in the seated posture than in the standing posture, and greater toe extension angles enhanced the windlass mechanism. These findings highlight the importance of intrinsic foot muscle training, such as towel curls, to improve MLA support and the windlass mechanism. Future studies should investigate their role in dynamic activities like walking.